Analysis of the effect of eco-efficiency on asset return in food and beverage manufacturing companies listed at the Johannesburg stock exchange - Malapa, Dimakatso Hellen (Managing global transitions, 2025)
This article examines the effect of eco-efficiency on corporate return on assets (ROA). The paper aimed to analyse whether corporate eco-efficiency performance (represented by energy consumption, water consumption, carbon emission and waste generation) affects the performance of ROA. Data on the eco-efficiency and ROA was collected from fourteen food and beverage companies listed in the Johannesburg Stock Exchange for a period of ten years (2012 to 2021). Using the STATA Software, the data was analysed by applying the Generalised Method of Moment (GMM) statistical technique, which enhanced the statistical analysis robustness. Findings from the GMM analysis showed different results. On the one hand, the results indicate that energy and water consumption in the food and beverage companies have a positive (but insignificant) effect on ROA. On the other hand, the results show that waste generation has a negative (but insignificant) effect on ROA; and that carbon emission has a negative and significant effect on ROA.
Keywords: carbon emission; donosnost sredstev; eco-efficiency; emisije ogljika; energy consumption; environmental accounting; financial performance; finančna uspešnost; nastajanje odpadkov; okoljska učinkovitost; okoljsko računovodstvo; poraba energije; poraba vode; prihodki od prodaje; return on assets; sales revenue; waste generation; water consumption